Efektivitas Penerapan Strategi Pemasaran Digital Dalam Meningkatkan Pangsa Pasar Pada UMKM Menyenk Café - Ariputra, Andy Atalla; Azhar, Ratih Mukti (Yayasan Daarul Huda Kruengmane, 2023)
Menyenk Café is a place selling food and drinks located in the Tenggilis Mejoyo area, like most other food and drink places, and according to its concept, Menyenk Café sells crushed chicken rice and mixed ice as its mainstay menu. In business activities, researchers found several problems in the quality of product sales and marketing. The aim of this research is to find out how the sale of food and beverage products influences the quality of product sales at Menyenk Café Tenggilis Mejoyo. The research method used is a qualitative approach method with in-depth interviews and data collection techniques based on the results of observations conducted at Menyenk Café. By Therefore, as a member of the UPN Veteran East Java Village Development team, we are trying to provide knowledge transfer in the form of how to improve the image or brand of Menyenk Cafe Tenggilis Mejoyo through digital marketing strategies to strengthen existence and reach a wider market, using social media as a promotional event and preparing product catalogs for map production capabilities and increase the market share of UMKM .